Role of Corporate Governance on the Performance of Insurance Companies of Nepal - Subedi, Sushil Dev (Journal of Business and Social Sciences Research, 2018)
The objective of this paper is to analyze the role of corporate governance on the financial performance of insurance companies. The study used descriptive cum causal relational research design. Firm ownership and board size are considered as the key variable of corporate governance while debt to equity ratio, firm size, firm age and firm growth are considered as control variables. The dependent variable firm performance is measured by return on asset (ROA) and return on equity (ROE). All the 40 insurance companies are considered as population of the study. The study used convenient sampling technique for selection of the sample. Seven out of 18 life insurance companies and eight out of 20 nonlife insurance companies are selected as sample. The study used five year data from 2009/10 to 2016/17 with 135 firm year observations. Data were collected from mail survey and published data from respective insurance company and Beema Samiti. Data were analyzed using a multiple linear regression model.The study concluded that corporate governance affects the firm performance in Nepalese insurance sector. Board size has a negative impact on ROA while firm size and firm ownership has a positive impact on ROA and ROE. The variable debt to equity has the negative and significant impact on ROE respectively.